2017
DOI: 10.1016/j.neuroscience.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of temporal prediction by electrical stimulation to the primate cerebellar nuclei

Abstract: The cerebellum is known to be involved in temporal information processing. However, the underlying neuronal mechanisms remain unclear. In our previous study, monkeys were trained to make a saccade in response to a single omission of periodically presented visual stimuli. To detect stimulus omission, animals had to predict the timing of each next stimulus. During this task, neurons in the cerebellar dentate nucleus exhibited a transient decrement of activity followed by a gradual increase in firing rate that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…We previously demonstrated that the periodic neuronal modulation in the cerebellar dentate nucleus depended on the stimulus interval, showing a greater firing modulation for longer ISIs (Ohmae et al, 2013; Uematsu et al, 2017). In this study, we also found that the magnitude of periodic activity in the caudate nucleus altered as the ISI was systematically varied from 100 to 600 ms. Like neurons in the cerebellum, a representative caudate neuron shown in Figure 4A exhibited greater firing modulation for longer ISIs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that the periodic neuronal modulation in the cerebellar dentate nucleus depended on the stimulus interval, showing a greater firing modulation for longer ISIs (Ohmae et al, 2013; Uematsu et al, 2017). In this study, we also found that the magnitude of periodic activity in the caudate nucleus altered as the ISI was systematically varied from 100 to 600 ms. Like neurons in the cerebellum, a representative caudate neuron shown in Figure 4A exhibited greater firing modulation for longer ISIs.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the activity of these neurons as well as behavioral parameters could be altered by systematic changes in the reward schedule. For example, the gradual rise of neuronal activity during stimulus repetition (Figure 3D), which likely reflected temporal expectation of the stimulus omission in each trial (Uematsu et al, 2017), might be scaled by the amount of reward. This possibility is to be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive behavior benefits from the ability to discern temporal regularities in the environment. To exploit these regularities, the brain must be able to measure time intervals between repetitive events ( Buhusi and Meck, 2005 ; de Lafuente et al, 2015 ; Confais et al, 2012 ; Leon and Shadlen, 2003 ; Grahn and Brett, 2007 ; Merchant and Lafuente, 2014 ; Merchant et al, 2015 ), and use this timing information to anticipate future events ( Goel and Buonomano, 2014 ; Jazayeri and Shadlen, 2010 ; Uematsu et al, 2017 ). This behavior is evident when we dance to music, which requires perceiving rhythms and generating movements in sync with them ( Levitin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive behavior benefits from the ability to discern temporal regularities in the environment. To exploit these regularities, the brain must be able to measure time intervals between repetitive events (Buhusi and Meck 2005; de Lafuente, Jazayeri, and Shadlen 2015; Confais et al 2012; Leon and Shadlen 2003), and use this timing information to anticipate future events (Goel and Buonomano 2014; Jazayeri and Shadlen 2010; Uematsu, Ohmae, and Tanaka 2017). This behavior is evident when we dance to music, which requires perceiving rhythms and generating movements in sync with them (Levitin, Grahn, and London 2018).…”
Section: Introductionmentioning
confidence: 99%